An investigation into transformation within the South African Mining Sector, with particular reference to the regulatory frameworks and mechanisms in which mining firms operate : a case study on Lonmin Plc - Edmond, Grant Malcolm (Department of Public Law, 2016)
Transformation is undoubtably a moral imperative. It primarily relates to the eradication of past discriminatory practices and the establishment of a society founded upon equality and justice. Unfortunately transformation has become a buzz word that is used in academic literature, legislation and the media I a variety of content. This research will focus on the mining sector, given the importance of the sector to the South African economy and the slow progress that the sector has made in advancing transformation. This dissertation sets out to better understand the term transformation through an extensive analysis of the current framework in which mining forms operate. This includes non-legislative and legislative documents. The research will take the form of a case study that focuses on Lonmin Plc. It will first conduct an extensive review of the literature and the transformation framework that applies. Secondly, the research will bring the case study into a current reality by interviewing individual miners, community leaders and Lonmin representatives. These interviews will be semi-structured, whereby an interview guide will form the base of the discussion. The goal of these interviews is to view the current transformation framework in light of the lived experiences of individuals. The interview data will be analyzed using a thematic analysis approach, initially coding the interview manuscripts and ultimately collating these codes into themes which will be discussed in detail. The research will focus on a Black Economic Empowerment deal that was concluded between Lonmin and the Bapo Community. The is intended to highlight some of the complexities surrounding Black Economic Empowerment deals in practice. The research found that the main components of transformation, as illustrated by the literature and the interviews, are the creation of better working conditions for miners, the skills development of Historically Disadvantaged South Africans, the adoption of preferential procurement policies by Lonmin Plc and the conducting of proper engagement processes between mining companies and mining communities.